ANALISIS PENGATURAN PENOLAKAN PEMBATALAN PERDAMAIAN STUDI KASUS KOPERASI SIMPAN PINJAM PRACICO INTI SEJAHTERA - Calvin, Calvin; Gultom, Elfrida Ratnawati (Ensiklopedia Education Review, 2024)
PKPU is an effort by the Debtor to avoid bankruptcy through debt restructuring. During the ratification of the PKPU settlement, it’s not uncommon for parties to disagree and seek to annul the settlement agreement. Creditors who disagree with the settlement during the creditor meeting can take legal actions such as cassation and judicial review. The core issue of this research is the regulation regarding a application for annulment of settlement after the ratification of the settlement deed or homologation in Bankruptcy and PKPU Law No. 37 of 2004 and Cooperative Law No. 25 of 1992 concerning cooperatives. This research employs a normative juridical method, which examines library materials and is descriptive in nature, aiming to describe through the collected data. The materials used are secondary materials, and the analysis is qualitative, along with drawing conclusions using deductive logic. This research includes the result that Supreme Court Decision No. 770 K/Pdt.Sus-Pailit/2022 not in conflict with the Bankruptcy and PKPU Law.Keywords: Savings and Loan Cooperative, Bankruptcy, Suspension of Debt Payment Obligations, Homologation